Influence of selected Socio-Economic Factors on Access to Agricultural Credit among Small-Scale Farmers in Nakuru County, Kenya - Martha W. Kariuki,; Agnes Oywaya-Nkurumwa; John G. Mwangi (Journal of Agricultural Extension Management, 2013)
Agricultural credit can be used to enhance farm productivity and to ensure sustainable food production. However, _most small-scale farmers in Nakuru County who need the credit cannot access it for various reasons and therefore its use remains low. This study sought to determine the influence of age. Gender, level of education and income on small-scale farmers’ access to agricultural credit in Nakuru County. The study used a cross-sectional survey research design to collect and analyse data. The results showed that farmers’ fear of being denied credit or not being able to repay were the majur reasons hindering them from borrowing. The researchers recommended that Kenva government through agricultural extension agents in collaboration with the financial institutions should provide farmers with information on agricultural credit and should establish cooperatives or credit associations through which small-scale farmers could borrow agricultural credit. Financial institutions offering agricultural credit should ensure agricultural loans are affordable. by reducing interest rates